Glocalization of the Sustainable Development Goals within the Legal Framework of Human Resource Development Policy: Glokalisasi Tujuan Pembangunan Berkelanjutan dalam Kerangka Hukum Kebijakan Pengembangan Sumber Daya Manusia - Marwah Hermansyah, Andi; Fichriyadi Hastira, Muh.; Pratama, Galank (Fakultas Hukum Universitas Jambi, 2025)
This article provides a critical analysis of the internalization of the values and objectives of the Sustainable Development Goals, particularly Goal 4 on Quality Education, within the human resource development policy framework as articulated in the 2021-2026 Regional Medium-Term Development Plan. Employing a normative legal research method grounded in literature review and political policy analysis, the study examines the characteristics of policy integration, the vertical and horizontal relationships among levels of government, and the dynamics between global development standards and local policy needs. The research draws upon official planning instruments, academic literature, and development reports, which were analyzed through thematic and discourse analysis to identify narrative constructions, policy rationalities, and the coherence between global objectives and regional policy orientations. The findings indicate that the incorporation of Quality Education objectives into regional planning documents remains predominantly administrative in nature, with a strong emphasis on quantitative indicators such as the provision of educational facilities and the qualifications of teaching personnel. In contrast, substantive dimensions at the core of the global agenda including equitable access to education, improvements in learning outcomes, inclusive pedagogical environments, and context-responsive capacity development for educators have not been positioned as central priorities in policy formulation. Furthermore, references to local cultural values appear merely declaratory and are not supported by operational or implementable frameworks. This article underscores the importance of adopting a glocalization-based approach that does not merely replicate global policy templates but instead reconstructs them through local values, empirical needs, and institutional capacities. Such an approach offers the potential to produce educational policies that are more responsive, equitable, and aligned with transformative human development objectives.